KOMUNIKASI PERSUASIF PEMERINTAH DESA DALAM MENGATASI PERNIKAHAN USIA DINI PADA MASYARAKAT DESA PERLABIAN KABUPATEN LABUHANBATU SELATAN - Siregar, Febri Shaleh; Sumanti, Solihah Titin (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This study focuses on the persuasive communication of the Perlave village government of South Labuhan Batu district, which is committed to early marriage in the local community. The research method used was a qualitative survey, collecting data through interviews with village officials and informants from the community who experienced early marriage. As a result, it was found that the main causes of early marriage in Perlavian villages were promiscuity and personal will. In addition, the Perrabian village government has implemented persuasive communication to overcome early marriage by raising awareness about the dangers of early marriage. These efforts were made to raise public awareness of the ill effects of early marriage and to encourage smarter decisions about marriage. This study provides an overview of the persuasive communication strategies used by the village government to combat early marriage in Perlav village. The results of this study are expected to provide a basis for village governments and related agencies to develop programs to more effectively address early marriage issues in the region.